2002
DOI: 10.1098/rspb.2002.2077
|View full text |Cite
|
Sign up to set email alerts
|

Gustatory sensilla sensitive to protein kairomones trigger host acceptance by an endoparasitoid

Abstract: Proteins isolated from the host cocoon of Acrolepiopsis assectella (Lepidoptera: Yponomeutoidea) act as kairomones for host acceptance by the endoparasitoid wasp Diadromus pulchellus Wesmael (Hymenoptera: Ichneumonidae). In this study, morphological, ultrastructural and electrophysiological studies were carried out in order to identify the contact chemoreceptive sensilla on the parasitoid antennae that perceive the protein kairomones. Three types of sensillum on the antennae of the females were found to have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 52 publications
(63 reference statements)
0
6
0
1
Order By: Relevance
“…The stimulus in oviposition can be unchained by WSMoL adsorption onto gustatory sensillas of A. aegypti female, as reported in a study on the detection of sex pheromones and protein kairomones by Glossina spp. and Diadromus pulchellus , respectively [45] , [46] . Volatile compounds were not detected by dynamic headspace analysis in WSMoL preparation indicating that, if present, they occurred in trace amounts.…”
Section: Discussionmentioning
confidence: 99%
“…The stimulus in oviposition can be unchained by WSMoL adsorption onto gustatory sensillas of A. aegypti female, as reported in a study on the detection of sex pheromones and protein kairomones by Glossina spp. and Diadromus pulchellus , respectively [45] , [46] . Volatile compounds were not detected by dynamic headspace analysis in WSMoL preparation indicating that, if present, they occurred in trace amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Plants are usually infested by multiple herbivores, which makes it challenging for natural enemies to select the target species. Herbivore contact kairomones are often speciesspecific, and therefore natural enemies generally rely on these non-volatile signals, which are examined by antennating or probing for recognition of hosts or prey (Vinson, 1998;Bénédet et al, 2002). These cues originate from various sources such as adult/larva/nymph body surfaces, larvae oral secretions, egg coating, and wing scales (Afsheen et al, 2008;Kaiser et al, 2017).…”
Section: Herbivore Contact Kairomones For Host/prey Recognition and Acceptancementioning
confidence: 99%
“…Parasitoid wasps, known to locate their suitable hosts in a complex environment are mediated largely by chemical cues. The cues associated with the host can be volatile substances that are perceived by olfaction sensilla at long distances, or contact substances that are mainly perceived by gustatory sensilla at close range 1 – 4 . Several studies showed that the chemosensory sensilla (olfaction and gustation) used by parasitoid wasps to locate and evaluate their hosts are mostly present on their antennae 4 – 7 .…”
Section: Introductionmentioning
confidence: 99%